Risk Management Assessment for Partnering Projects in the Malaysian Construction Industry - Adnan, Hamimah; Rahmat, Mohd Nidzam; Mazali, Nur Fatanah Nadiah; Jusoff, Kamaruzaman (2008)
The Partnering concept is not a new way of doing business. The partnering process establishes the working relationship among the parties (stakeholders) through a mutually-developed, formal strategy of commitment and communication. It attempts to create an environment where trust and teamwork prevent disputes, co-operative bonds are fostered for everyone’s benefit and the completion of successful project is facilitated. The Construction industry in Malaysia is suffering constraints in the processes of construction procurement. Thus, partnering is used as an approach in procurement that could lead toward improving performance of the construction industry in Malaysia. Organizations which have used partnering for construction projects are now reporting favourable results, which include the decreased costs, quality improvement and delivery of project to programme. Partnering has reached many benefits in terms of project cost, time quality, build ability and etc. Despite the benefits in applying the partnering procurement method, there remains risks associated with this mode of construction.